Why Trade Facilitation Matters to Africa - Portugal-Perez, Alberto (Washington, DC: World Bank, 2012)
This paper reviews data and research on trade costs for Sub-Saharan African countries. It focuses on: border-related costs, transport costs, costs related to behind-the border issues, and the costs of compliance with rules of origin specific to preferential trade agreements. Trade costs are, on average, higher for African countries than for other developing countries. Using gravity-model estimates, the authors compute ad-valorem equivalents of improvements in trade indicators for a sample of African countries. The evidence suggests that the gains for African exporters from improving the trade logistics half-way to the level in South Africa is more important than a substantive cut in tariff barriers. As an example, improving logistics in Ethiopia half-way to the level in South Africa would be roughly equivalent to a 7.5 percent cut in tariffs faced by Ethiopian exporters.